HISTOCHEMICAL OBSERVATIONS ON THE VITELLOGENESIS IN THE MARINE CRAB, PORTUNUS SANGUINOLENTUS (CRUSTACEA:BRACHYURA) - BABU, B. TRINADHA; LALITHA, M.; SHYAMASUNDARI, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Histochemical observations of Ooplasm and yolk granules in different stages of oocyte maturation in the ovary are made in the marine crab, Psanguinolenius. Four principal stages of oocytes are observed. The first stage of oocyte possesses a big nucleus and the Ooplasm shows basophilic nature. In second stage oocyte perinuclear ring is formed and the vitellogenesis commences with the accumulation of glycogen and RNA. The third and fourth stage oocytes are characterised by the presence of carbohydrate-protein lipid bodies, The chemical nature of the follicle cells is also studied and comments are made on their possible role in vitellogenesis. Based on the histochemical nature of oocytes and follicle cells, an autoheterosynthetic mode of yolk formation is proposed in this crab.